Analisis tingkat kesehatan keuangan perusahaan BUMN di bidang konstruksi - Elza Levina Syahda; Ningrum Pramudiati (Qualitative Research of Business and Social Sciences, 2024)
This study analyzes State-Owned Enterprises (BUMN) financial health in the building construction sector, specifically PT. WIKA, during the period from 2017 to 2023.  This analysis is conducted to improve the company's financial performance using eight financial indicators established in the Minister of BUMN Decree No: Kep-100/MBU/2002. The research results show that in 2023, PT. WIKA received the "Unhealthy" designation, with a final weighted score of 29.13%, indicating a significant decline in the Return on Equity (ROI) and Return on Investment (ROI) ratios. (ROI).  This decline is caused by increased liabilities and decreased equity, which hinder debt management and operational efficiency.  In addition, horizontal and vertical analysis also revealed that the company is experiencing difficulties maintaining stable financial performance in asset management.  This research proposes recommendations for improvement, including enhancing operational efficiency, improving debt management, and leveraging technology for data visualization to support more accurate decision-making.  The results of this research are expected to assist in the management of PT and provide insights. WIKA is undertaking efforts to improve the company's financial health.